Application of stepwise data envelopment analysis and grey incidence analysis to evaluate the effectiveness of export promotion programs - Hajiagha, Seyed Hossein Razavi; Zavadskas, Edmundas Kazimieras; Hashemi, Shide Sadat (Journal of Business Economics and Management, 2013)
Export promotion programs are incentives to increase the participation of companies in international markets. On the other hand, governments try to help exporting companies with developing their goal markets. Therefore, for this purpose, many different programs have been created. To show the effectiveness of these programs, the paper refers to stepwise DEA and grey incidence analysis. Finally, the article determines a unified ranking of the applied programs that can be used by decision makers for resource allocation considering different types of programs based on their effectiveness.